Study on Viability and Effect of Liquid Formulation of Bacillus subtilis, Bbv 57 Against Nematode - Fungus Disease Complex in Tomato, Lycopersicon esculentum Mill. (Indian Journal of Nematology, 2024)
Viability of antagonistic Bacillus subtilis isolate, Bbv 57 was observed in nutrient broth (NB) amended with different chemicals viz., glycerol (10 mM), trehalose (10 mM) and polyvinylpyrrolidone (PVP) (2 %). Among different chemical amendments tested, NB amended glycerol (10 mM) maintained Bbv 57 population for a period of one year. Liquid formulation of Bbv 57 was prepared by adding log phase culture of the bacterium in NB amended glycerol and further tests were carried out with this formulation. In vitro, minimum egg hatching and maximum juvenile mortality of Meloidogyne incognita and minimum mycelial growth of Fusarium oxysporum f. sp. lycopersici was observed in 5 day old formulation of Bbv 57 when compared to formulations with different ages. In pot culture and field studies, maximum plant growth parameters of tomato, minimum nematode population and fungus colonies were recorded with soil drenching of liquid formulation of Bbv 57 (1000 ml / ha).